PENGGUNAAN GARAM, SUKROSA DAN ASAM SITRAT KONSENTRASI RENDAH UNTUK MEMPERTAHANKAN MUTU FILLET IKAN GABUS (Channa striata) - Zainona Ratnasari; Ace Baehaki; Agus Supriadi (Universitas Sriwijaya, 2014)
The purposes of research were to maintain the quality of snakehead fillet and to know the effect of low concentration addition salt, sucrose and citric acid and different storage time on the quality of snakehead fillet stored at 40C. The experiment was arramged in a randomized block factorial design with two replications. The first factor was different solvent addition, the second factor was storage time. Observation parameters included physical analysis (WHC), chemical analysis (TVB) and microbiological analysis (TPC). The result showed that the value of WHC, TVB and TPC on A2 factor has lower than the other factors. The value of WHC, TVB and TPC increased during storage. The limit total of microbes was permissible for A0 treatment until day 9th is 5.60 log10 cfu/g (3.9 x 105), A1 until day 9th is 5.46 log10 cfu/g (2.9 x 105), while A2 treatment until day 18th is 5.60 log10 cfu/g (3.9 x 105).